Influence of the Smile Line on Smile Attractiveness in Short and Long Face Individuals - Amjad Al Taki; Thar Hayder Mohammed; Ahmad Mohammad Hamdan (International Journal of Dentistry)
Objectives. The study assessed the impact of facial height on attractiveness of smile, in association with the maxillary gingival display. This research was performed by dental professionals and laypersons. Materials and Methods. Frontal extraoral photographs were captured for both short and long faces. The photographs were modified using software for image-processing and three rater groups (orthodontists, dentists, and laypersons) evaluated the smile attractiveness, with 30 subjects in each group. Differences in ratings of the different smiles among the different experimental groups were examined using the Kruskal-Wallis test. The Mann–Whitney U test was performed for pairwise comparisons between the experimental groups. Results. Dentists and laypeople were most likely to agree. For the short face, laypeople and dentists both rated the +2 mm gingival display smile as the most attractive smile whilst orthodontists ranked the 0 mm gingival display smile as the most attractive smile. For the long face, laypeople and dentists ranked the 0 mm gingival display smile as the most attractive smile, whilst orthodontists ranked the +2 mm gingival display as the most attractive. Conclusion. Smile line of both short and long face subjects was found to influence the smile attractiveness rating by the three rater groups.